Uptake and molecular impact of aluminum-containing nanomaterials on human intestinal caco-2 cells. Issue 9 (21st October 2018) - Sieg, Holger; Braeuning, Caroline; Kunz, Birgitta Maria; Daher, Hannes; Kästner, Claudia; Krause, Benjamin-Christoph; Meyer, Thomas; Jalili, Pégah; Hogeveen, Kevin; Böhmert, Linda; Lichtenstein, Dajana; Burel, Agnès; et al.
Abstract: Aluminum (Al) is one of the most common elements in the earth crust and increasingly used in food, consumer products and packaging. Its hazard potential for humans is still not completely understood. Besides the metallic form, Al also exists as mineral, including the insoluble oxide, and in soluble ionic forms. Representatives of these three species, namely a metallic and an oxidic species of Al-containing nanoparticles and soluble aluminum chloride, were applied to human intestinal cell lines as models for the intestinal barrier. We characterized physicochemical particle parameters, protein corona composition, ion release and cellular uptake. Different in vitro assays were performed to determine potential effects and molecular modes of action related to the individual chemical species. For a deeper insight into signaling processes, microarray transcriptome analyses followed by bioinformatic data analysis were employed. The particulate Al species showed different solubility in biological media. Metallic Al nanoparticles released more ions than Al2 O3 nanoparticles, while AlCl3 showed a mixture of dissolved and agglomerated particulate entities in biological media. The protein corona composition differed between both nanoparticle species. Cellular uptake, investigated in transwell experiments, occurred predominantly in particulate form, whereas ionic Al was not taken up by intestinal cell lines. Transcellular transport was not observed. None of the Al species showed cytotoxic effects up to 200 µg Al/mL. The transcriptome analysis indicated mainly effects on oxidative stress pathways, xenobiotic metabolism and metal homeostasis. We have shown for the first time that intestinal cellular uptake of Al occurs preferably in the particle form, while toxicological effects appear to be ion-related.